Service priority-aware network traffic scheduling mechanism - Huahui LV; Zhida LIN; Hongcong HUANG (Dianxin kexue)
In view of the problem that network congestion which caused by the uneven distribution in large traffic data,a priority-aware dynamic network traffic scheduling mechanism was proposed.By using the token bucket algorithm,different buckets of different rates were assigned to different services according to the service priorities.The priorities of the service and the remaining buffer space of the user nodes was taken into account to deal with different services.At the same time,the traffic arrival factor,service factor and node cache were regarded as target to define a network traffic scheduling mechanism performance indicator:packet loss rate.The numerical results show that the proposed mechanism can rationally divide the service priorities in the network,effectively utilize the network resources,prevent the network congestion,enhance the network performance,and provide the users with more stable and reliable network service.